2019
DOI: 10.3390/math7030244
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model and Numerical Solution of a Boundary Value Problem for a Multi-Structure Plate

Abstract: This study examined the deformation problem of a plate system (formed side-by-side) composed of multi-structure plates. It obtained numerical approaches of the transmission conditions on the common border of plates that composed the system. Numerical examples were solved in different boundary and transmission conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In this study, the transmission conditions obtained on the common border of the plates that constituted the system in our previous study [22] are extended for a system consisting of plates with different mechanical properties, and the finite difference expressions of these conditions are given. It is the aim of this study to determine how long the sizes of the plates should be for obtaining the desired amount of bending against the force affecting the system under different boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the transmission conditions obtained on the common border of the plates that constituted the system in our previous study [22] are extended for a system consisting of plates with different mechanical properties, and the finite difference expressions of these conditions are given. It is the aim of this study to determine how long the sizes of the plates should be for obtaining the desired amount of bending against the force affecting the system under different boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Once Hopf bifurcation occurs, the panel will oscillate for ever, which is known as panel flutter. Zhang et al investigated both the local and global bifurcations of a rectangular, thin plate [10]. Ye studied the nonlinear aeroelastic flutter and stability of the panel [11].Yang et al also provided a study on the nonlinear thermal flutter of heated curved panels in supersonic air flow using the Newton iterative approach and Runge-Kutta method [12].…”
Section: Introductionmentioning
confidence: 99%
“…The governing equation thus obtained and the variation of material properties along certain directions, due to the incorporation of functionally-graded materials, make analytical solving more and more difficult. It has been found that even for a plate consisting of classical materials, the analytical solution is hard to obtain, and in most cases, numerical simulations have to be resorted to (for example, see recent studies [22,23]). Therefore, seeking an effective analytical technique, especially since the structural property of the analytical solution may clearly show the electromechanical coupling effect in the final results, seems to be valuable and urgent.…”
mentioning
confidence: 99%